Neuroarthropathy of the Foot and Ankle - Banskota, B; Bijukachhe, B; Shrestha, BK; Banskota, AK (Nepal Orthopaedic Association Journal, 2013)
DOI: http://dx.doi.org/10.3126/noaj.v1i1.8131 Nepal Orthopaedic Association Journal Vol.1(1) 2010